The cost of natural gas shortages in Ireland - Eimear Leahy; Conor Devitt; Seán Lyons; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2011)
This paper investigates the economic implications of disruptions of one to ninety days to the supply of natural gas in Ireland. We assess the impact of a hypothetical gas supply disruption in both winter and summer in 2008 (with observed market characteristics) and in 2020 (with projected market characteristics). The cost of a natural gas outage includes the cost of natural gas being unavailable for heating and other purposes in the industrial and commercial sectors, lost consumer surplus in the residential sector, the cost of lost electricity in all sectors and lost VAT on the sale of gas and electricity. Ireland produces much of its electricity from natural gas and the loss of this electricity accounts for the majority of the cost of a natural gas outage. Losing gas-fired electricity would cost 0.1 to 1.0 billion euro per day, depending on the time of week, the time of year, and rationing of electricity. Industry should be rationed before households to minimize economic losses, but current emergency protocols favour industry. If gas-fired electricity is unavailable for three months, the economic loss could be up to 80 billion euro, about half of Gross Domestic Product. Losing gas for heating too would add up to approximately 8 billion euro in economic losses. We also discuss some options to increase Ireland's security of supply, and find that the cost is a small fraction of the avoided maximum damage.
Keywords: 330; security of supply; natural gas; value of lost load; Ireland; Energiekonsum; Erdgas; Angebot; Produktsubstitution; Rationierung; Wohlfahrtsanalyse; Prognose; Irland